Safety and labour conditions: The accord and the national tripartite plan of action for the garment industry of Bangladesh - Mohd Raisul Islam Khan; Christa Wichterich (International Labour Organization (ILO), 2015)
The factory fire at Tazreen Fashions in 2012 and the collapse of the Rana Plaza in 2013 generated a huge outcry about the working conditions and labour relations in the Readymade Garment (RMG) industry in Bangladesh, and led to the adoption of the multi-stakeholder agreements Accord on Fire and Building Safety in Bangladesh (Accord) at the international level and the National Tripartite Plan of Action (NTPA) at the domestic level. This paper investigates how the Accord and the NTPA have been implemented in the first two years after their adoption, whether they have contributed to an overall improvement in safety and labour conditions as well as to organizing in the RMG sector, and whether they can be considered as a "major breakthrough" and "game changer". The empirical research highlights the scope and limitations of the coverage of the two agreements. The findings indicate that after an initially good take-off, the activities lost pace and intensity and the remediation came almost to a standstill. The main assumption of the analysis of the Accord and NTPA implementation is that this process, its pace, results and constraints are consequences of the underlying power structures of the transnational apparel chains and the actual imbalance of power among the stakeholders.
Keywords: 330; occupational safety; plan of action; clothing industry; Bangladesh